Structural, optical and electrical properties of Cu2ZnSnS4 films prepared from a non-toxic DMSO-based sol-gel and synthesized in low vacuum. (January 2017) - Orletskyi, I.G.; Solovan, M.M.; Brus, V.V.; Pinna, F.; Cicero, G.; Maryanchuk, P.D.; Maistruk, E.V.; Ilashchuk, M.I.; Boichuk, T.I.; Tresso, E.
Abstract: This paper reports a complex analysis of structural, optical and electrical properties of Cu2 ZnSnS4 (CZTS) films, prepared by spin-coating of a sol-gel based on the low-cost and environmentally friendly solvent dimethyl sulfoxide (DMSO) and synthesized in low vacuum (0.1 Pa). The effect of a short-term low-temperature treatment in air and final annealing under low vacuum (0.1 Pa) on the synthesis of CZTS films was tested and analyzed. XRD and Raman spectra have shown the polycrystalline nature of obtained CZTS films with almost a pure kesterite phase content. The average size of crystallites D 60 nm in the films was estimated. The value of the band gap E g ≈1.53 eV was determined from the analysis of optical characteristics. The analysis of electrical characteristics was carried out in the scope of the model of current transport in polycrystalline materials with electrically active grain boundaries. The determined values of the specific resistance ρ ≈2.38 Ω cm, the hole density p 0 ≈4.2×10 18 cm −3 and the effective mobility μ p ≈0.63 cm 2 /(V s) demonstrate that the CZTS films under investigation are prospective for the fabrication of highly efficient solar cells. Graphical abstract: Highlights: Non-toxic DMSO solvent and high temperature synthesis of CZTS films in low vacuum. The average size of crystallites in the single phase CZTS films was about 60 nm. Current transport in the CZTS films is governed by the thermionic emission over potential barriers at grain boundaries.